Pengaruh Kemampuan Inteligensi dan Task Commitment Terhadap Prestasi Belajar Matematika - Febryanti Febryanti (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2017)
This study is based on the number of children who actually have the potential to achieve high learning, but it has low achievement, because some factors that do not have, such as task commitment. This study aims to determine how the influence of intelligence and task commitment to the achievement of learning mathematics students SMPN 4 Sendana. This research type is correlation research. The population in this study is the students of class VIII SMP Negeri 4 alone. Sampling technique used "Purposive Sampling". Data collection techniques used questionnaires and documentation. While the data analysis technique is a quantitative analysis, which uses multiple regression techniques. The results of this study indicate that the ability of intelligence to positively affect the mathematics learning achievement of students class VIII SMPN 4 Sendana, with regression coefficient - 0.110 with a significant level of 0.516 and t arithmetic of -0.657. task commitment has a positive effect on student learning achievement, with regression coefficient equal to - 0,053 with significant level 0,422 and t count equal to -0,812. together intelligence ability and task commitment have an effect on student's mathematics learning achievement, with F count 0,460 at significant level 5% (0,05) value p = 0,635.